Antioxidants-Related Superoxide Dismutase (SOD), Catalase (CAT), Glutathione Peroxidase (GPX), Glutathione-S-Transferase (GST), and Nitric Oxide Synthase (NOS) Gene Variants Analysis in an Obese Population: A Preliminary Case-Control Study - Amani M. T. Gusti; Safaa Y. Qusti; Eida M. Alshammari; Eman A. Toraih; Manal S. Fawzy (Antioxidants, 2021)
Oxidative stress and antioxidants play an important role in obesity etiopathology. Genetic variants, including single nucleotide polymorphisms (SNPs) of the antioxidant-related genes, may impact disease risk in several populations. This preliminary study aimed to explore the association of 12 SNPs related to superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), glutathione-S-transferase (GST), and nitric oxide synthase (NOS) genes with obesity susceptibility in a Saudi population. A total of 384 unrelated participants, including 154 (40.1%) obese individuals, were enrolled. TaqMan OpenArray Genotyping assays were used. Six SNPs were significantly more prevalent in obese cohorts: (1) GSTM1 rs1056806*C/T; (2) SOD1 rs2234694*A; (3) SOD2 rs4880*G; (4) SOD3 rs2536512*A; (5) GPX1 rs1800668*A; (6) NOS3 rs1799983*G. Four SNPs were associated with higher obesity risk under heterozygote and dominant models for GSTM1 rs1056806 (C/T), homozygote model for SOD2 rs4880 (A/G), and homozygote and recessive models for GPX1 rs1800668 (A/G). In contrast, SOD3 rs2536512 (A/G) were less likely to be obese under heterozygote and dominant models. The CGAG, CAAA, TGGG, and CGAG combined genotypes showed a higher risk of obesity. In conclusion, the present results suggest that oxidative-stress-related genetic determinants could significantly associate with obesity risk in the study population.